Navigating Risks: A Comprehensive Functional Hazard Assessment of eVTOL Power Battery Systems (London Journal of Engineering Research, 2024)
With the advancement of the power battery and electric propulsion technology, the versatile redundancy enables the eVTOL aircraft design to be more reliable and cost-effective, thereby to be safer. This mandate the conducting of systematic aircraft level safety mitigation and comprehensive functional hazard assessment to ensure a fail-safe design, and process assurance to address the potential development errors in a pragmatic manner. After describing the application scenarios of eVTOL, the safety mitigation effects of applyingcrashworthiness and ballistic rescue system (BRS) on eVTOL aircraft were analyzed and elaborated, and the flight profile of eVTOL was refined based on the aircraft level safety objectives. Utilizing the commercial aircraft system engineering approach, an aircraft level functional hierarchy was proposed for eVTOL, emphasizing completeness and correctness. Insight of the innovative features of the electric power battery system, the well-established aircraft functional hazard assessment (FHA) methodology was deployed to scrutinize thefunctional inventory. Utilizing the conventional power battery system architecture found in Electric Vehicle (EV), the pertinent functions of the eVTOL's power battery system have been allocated in order to identify potential weaknesses and opportunities for improvement from a safety perspective in extant EV power battery systems. Suggestions were made after discussions that, prior to installing existing power battery systems into eVTOL aircraft applications, developers must not only enhance the availability, reliability, and safety of the battery system, but also identify and mitigate single-point failures and design errors within the extant battery system to substantiate the compliance to safety courses in airworthiness regulations.
Keywords: TELEMAC; SISYPHE; bed roughness; Shield coefficient; bed load transport formulae; Gain Size; hydromorphological modeling; sediment transport; numerical simulation; river engineering.; Incubator; robust diagnosis; bond graph approach; linear fractional transformations; analytical redundancy relations; fiber content; RC beams; Flexural strength; SFRC; Steel fiber; Volume fraction.